The Maximum Effectiveness of Finding the Lexical Definition through Obscurity and Circularity - wijayanti, nurvita (Lire Journal (Journal of Linguistics and Literature), 2017)
This paper shows the two problems namely circularity and obscurity relating to dictionary definition and its solutions. The two problems are mostly attached in the definition from both online and written dictionary of Longman Dictionary of Contemporary English. The topic is chosen since it contains the daily problem encountered when consulting the dictionary. The data are collected by showing the words that have circularity and obscurity each of them are twenty words. Next, the data is analyzed through the high frequency of words that contains both problems. The solutions are also offered for both the word-seekers and the lexicographers to get the better definition in the future. Facing the problem of circularity, it is better to the word-seekers to collect the information from the words and combine them into good information. The obscurity can be solved into two ways namely controlled defining vocabulary and full-sentence definition. Lastly, the writer suggest to the next researchers to gain more data and solution to get the better revision.